Real effects of foreign exchange risk migration: Evidence from matched firm-bank microdata - Puriya Abbassi; Falk Bräuning (Federal Reserve Bank of Boston, 2020)
When firms trade forward contracts with banks to protect foreign currency cash flows against exchange rate movements, foreign exchange risk migrates to the banking sector. We show how this migrated risk may induce systemic repercussions with severe implications for the real economy. For identification, we exploit the Brexit referendum in June 2016 as a quasi-natural experiment in combination with detailed microdata on forward contracts and the credit register in Germany. Before the referendum, firms substantially increased their use of derivatives in response to the heightened uncertainty; banks, in providing these contracts, did not fully intermediate the risk and retained a large share of it on their own books. The depreciation of the British pound in response to the referendum's outcome posed a shock to the capital of ex ante exposed banks. Banks, especially weakly capitalized ones, absorbed these losses by cutting back credit to all firms, including those unlikely to have had any exchange rate exposure to begin with. Firms that had ex ante borrowing relationships with banks facing losses experienced a larger reduction in credit and a greater decline in investment compared with their industry peers, thereby contributing to the aggregate investment contraction. We also find these effects to be more pronounced for small firms, which is consistent with credit market frictions being rooted in asymmetric information problems.
Keywords: D53; D61; F31; G15; G21; G32; 330; credit supply; foreign exchange risk; financial intermediation; risk migration; financial stability